Identification and analysis of key components in the efficiency of the use of radiation in rice: Doctoral thesis abstract - Quero Corrallo, Gastón Eduardo; Borsani Cambón, Julio Omar (Agrociencia Uruguay, 2020)
<span data-sheets-root="1" data-sheets-value="{"1":2,"2":"One of the main limitations of rice yield in regions of high productive performance is the light-use efficiency (LUE). LUE can be determined at the whole-plant level or at the photosynthetic apparatus level (quantum yield). The aim of this thesis was to analyze the cultivar dependence regarding LUE at the plant level and quantum yield using four rice cultivars and four light environments. To achieve this, two in-house Light Systems were developed: Light System I which generates white light environments (spectral quality of 400–700 nm band) and Light System II which generates a blue-red light environment (spectral quality of 400–500 nm and 600–700 nm bands). Energy partition in PSII was determined by the quantum yield of three de-excitation processes using chlorophyll fluorescence parameters. The damage of PSII was only increased by low levels of energy in white environments, leading to a decrease in photochemical processes due to the closure of the reaction centers. In conclusion, all rice cultivars evaluated in this study were sensible to low levels of radiation, but the response was cultivar dependent. There was not a clear genotypic relation between LUE and quantum yield. Through a GWAS strategy, 32 genes of rice genome associated with the main parameters that define the quantum yield of PSII in rice were identified. Our work shows the association between light-harvesting complexes and the potential quantum yield of PSII, as well as the relationship between regions that code for PSI-linked proteins in energy distribution during the photochemical process of photosynthesis. This thesis opens new lines of work focused on establishing the mechanisms of action of the spectral quality of light in PSI and how this defines the energy partition of PSII."}" data-sheets-userformat="{"2":14653,"3":{"1":0,"3":1},"5":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"6":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"7":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"8":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"11":4,"14":{"1":2,"2":0},"15":"Calibri","16":11}">One of the main limitations of rice yield in regions of high productive performance is the light-use efficiency (LUE). LUE can be determined at the whole-plant level or at the photosynthetic apparatus level (quantum yield). The aim of this thesis was to analyze the cultivar dependence regarding LUE at the plant level and quantum yield using four rice cultivars and four light environments. To achieve this, two in-house Light Systems were developed: Light System I which generates white light environments (spectral quality of 400–700 nm band) and Light System II which generates a blue-red light environment (spectral quality of 400–500 nm and 600–700 nm bands). Energy partition in PSII was determined by the quantum yield of three de-excitation processes using chlorophyll fluorescence parameters. The damage of PSII was only increased by low levels of energy in white environments, leading to a decrease in photochemical processes due to the closure of the reaction centers. In conclusion, all rice cultivars evaluated in this study were sensible to low levels of radiation, but the response was cultivar dependent. There was not a clear genotypic relation between LUE and quantum yield. Through a GWAS strategy, 32 genes of rice genome associated with the main parameters that define the quantum yield of PSII in rice were identified. Our work shows the association between light-harvesting complexes and the potential quantum yield of PSII, as well as the relationship between regions that code for PSI-linked proteins in energy distribution during the photochemical process of photosynthesis. This thesis opens new lines of work focused on establishing the mechanisms of action of the spectral quality of light in PSI and how this defines the energy partition of PSII.